Development of Simultaneous Pressure and Velocity Measurements Using Multi-Luminophore Microspheres for Wind Tunnel Application - Pryor, Lillian Stroh (My University, 2015)
The development of pressure-sensitive microbeads allows for simultaneous measure- ment of pressure and velocity. These aerosolized microbeads are loaded with a pressure-sensitive dye coupled with a pressure-insensitive reference dye to provide pressure measurements. Methods of fabricating these particles and the results from their response times, characterized using a shock tube facility, are presented and dis- cussed. Imaging techniques of these particles are developed and are used for creating Stern-Volmer plots for each of the particle types developed by measuring the intensi- ties of the pressure-sensitive dye normalized to those of the reference dye and then to a baseline condition intensity ratio. Light intensity from the microspheres is measured using EMCCD cameras and processed to back-calculate pressure. A PIV camera is used to measure light intensity from the reference dye and in the future will be used to track the particles velocities. Further results regarding technique development will be discussed.
Thesis (Master's)--University of Washington, 2015
Keywords: aerosolized; pressure-sensitive; psp; Aerospace engineering; Engineering; aeronautics and astronautics